2014
DOI: 10.1111/rec.12094
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Size Dependent Facilitations from the Native Shrub Rhodomyrtus tomentosa to the Early Establishment of Native Trees Castanopsis fissa and Syzygium hancei in Tropical China

Abstract: The quantitative role of the canopy size of nurse shrubs on microenvironment and native tree establishment in degraded tropical lands has been seldom studied. In a 21-month field experiment, we aimed to test the effect of a native shrub with different canopy sizes on the early establishment of native trees as part of the effort of forest restoration in tropical China. We examined the microenvironment, and the seedling establishment and growth of two native trees: Castanopsis fissa and Syzygium hancei in both o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…These findings are in agreement with those reported in other facilitation studies carried out in tropical forest (Melo et al 2015;Souza et al 2015;Bueno and Llambí 2015). These results may be due to several mechanisms induced by nurse plants, such as improvements in soil conditions (Liu et al 2014;Ramírez et al 2015;Mihoč et al 2016), favorable microclimate (Bueno and Llambí 2015;Ramírez et al 2015), protection from herbivores (Gómez-Aparicio et al 2004) and reduced competition with herb species (Avendanõ-Yáñez et al 2014). In addition, tree species can attract seed dispersing animals, such as birds that use the branches as perches, increasing rainfall of seeds below their canopies (Aukema and Martinez del Rio 2002;Duarte et al 2006;Zwiener et al 2014).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are in agreement with those reported in other facilitation studies carried out in tropical forest (Melo et al 2015;Souza et al 2015;Bueno and Llambí 2015). These results may be due to several mechanisms induced by nurse plants, such as improvements in soil conditions (Liu et al 2014;Ramírez et al 2015;Mihoč et al 2016), favorable microclimate (Bueno and Llambí 2015;Ramírez et al 2015), protection from herbivores (Gómez-Aparicio et al 2004) and reduced competition with herb species (Avendanõ-Yáñez et al 2014). In addition, tree species can attract seed dispersing animals, such as birds that use the branches as perches, increasing rainfall of seeds below their canopies (Aukema and Martinez del Rio 2002;Duarte et al 2006;Zwiener et al 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Nurse plants can reduce the amount of light that reaches the soil and thus reduce its temperature (Padilla and Pugnaire 2006;Lima and Gandolfi 2009). Nurse plants are responsible for increasing the availability of water, as well as improving the levels of nutrients available in the soil through the liberation of organic material under their canopies (Koorem and Moora 2010; Liu et al 2014;Ramírez et al 2015;Mihoč et al 2016;Pueyo et al 2016). Nurse plants also provide protection from herbivores (Gómez-Aparicio et al 2004) and reduce competition with herb species (Avendanõ-Yáñez et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by Rodríguez-Calcerrada et al (2008) for Quercus petraea and Q. pirenaica, also non-succulent plants. Liu et al (2014) also studied the beneficial effects of a native shrub (Rhodomyrtus tomentosa) on seedling establishment of two tree species in Tropical China. They found that photoinhibition was reduced for Castanopsis fissa seedlings under medium canopies and for Syzygium hancei seedlings under large canopies.…”
Section: Discussionmentioning
confidence: 99%
“…In arid and semi-arid ecosystems, shrubs are conducive to the increase in the number of herb-layer plant species [4]. In subtropical forests, shrubs facilitate the growth of understory tree seedling [5,6]. In reclaimed mined sites, shrubs act as ecosystem engineers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, changes in the light environment could be one of the main reasons. Furthermore, there are various optimum light levels for the growth of different shrubs [6,58]. For example, G. jasminoides showed its optimum growth rate above 52% sunlight [49], and there was a very rigorous light demand by B. frutescens [59].…”
mentioning
confidence: 99%